Study on Yield Gap and Prioritization of Castor production Constraints for semi-arid regionin Gujarat - A.K. Rai, S. Khajuria, Kanak Lata, Rajkumar; J.K. Jadav (Indian Journal of Extension Education, 2018)
Castor (Ricinuscommunis L.) is as one of the most important oil crops of the Panchmahal district of Gujarat. However, its productivity of castor in the district is very low. Attempts are made to improve productivity and to increase area under castor by adopting HYVs. In order to compare conventional castorvarieties withHYVs, 75 front line demonstrations were carried out in systematic manner on farmers’ field to show the worth of a HYVsin comparison to local varietiesand thereby convincing farmers about potentialities of improved production management practices of castor for further adoption, involving feasible and effective scientific package of practices. The demonstrations clearly showed enhancement of productivity, at the same time area under castor cultivation was also noticed to be enhanced. The yield was found to be increase from 1980kg/ha in local varieties to 2990kg/ha in demonstrations. Similarly, the benefit cost ratio for HYVswas found to increase to 3.4 as compared to local varieties (2.5). The economic and benefit cost ratio can be further improved to 3.8 by giving slightly higher inputs for cultivation and marketing. The impact of FLDs was analyzed which showed improvement of knowledge and satisfaction of farmers as the main reason for mass scale adoption.